Public perception on safe city programmes in Malaysia / Mohd Syahfiq Tukijan and Jesslynda Sicily Duali - Tukijan, Mohd Syahfiq; Duali, Jesslynda Sicily
Safe city refers to the idea in the community that uses technology to help the government and the community to reduce crime rates as well as create a safe and comfortable environment for the community. A safe city is also a livable environment in the context of sustainability where it is able to preserve the city for the quality of life of the community. The existence of a safe city is said to be able to reduce the problems found in urban areas such as vandalism, threatening public safety and roads as well as public health. The purpose of this study is to identify the level of effectiveness of safe city programs, determine the importance of safe city programs and identify facilities or actions to reduce crime rates based on the concept of safe cities among communities in Malaysia. This study was conducted using quantitative methods and non -probability sampling, sampling facilities in collecting data by distributing questionnaires to the community from all states in Malaysia. Based on the findings of the study, factors such as crime rates, vandalism, public safety and health as well as road safety influence the effectiveness of the implementation of safe city programs in Malaysia. Therefore, this study can provide benefits to the government to implement the safe city program more effectively in reducing the problems in the city.